Limbic response to stress linking life trauma and hypothalamus-pituitary-adrenal axis function. (January 2019) - Seo, Dongju; Rabinowitz, Arielle G.; Douglas, Ryan J.; Sinha, Rajita
Highlights: Higher life trauma exposure was significantly associated with lower basal cortisol levels. Increased response to stress in limbic-medial temporal lobe (MTL) regions was associated with higher trauma scores and low basal cortisol. Increased response to stress in limbic-MTL regions mediated the relationship between trauma and low basal cortisol levels. Abstract: Trauma alters neuroendocrine responses to stress and increases vulnerability to stress-related disorders. Yet, relationships among trauma, stress-induced neural changes and hypothalamic–pituitary–adrenal (HPA) axis activity have not been determined. The present study used functional magnetic resonance imaging to investigate the impact of life trauma on basal cortisol levels and neural responses to acute stress in 73 healthy individuals during brief stress and neutral-relaxing imagery using a well-established, individualized imagery method. We hypothesized that trauma experience would have a negative impact on brain function, resulting in altered basal cortisol levels via dysregulated neural control over the HPA axis system. Results showed that higher life trauma exposure was significantly associated with lower basal cortisol levels. Neuroimaging results indicated that both higher life trauma and low morning cortisol levels were associated with increased response to acute stress in limbic-medial temporal lobe (MTL) regions including the amygdala and hippocampus. A mediation analysis showed that increased limbic-MTL response to stress mediated the relationship between life trauma and low cortisol levels. Findings revealed a significant impact of lifetime trauma on neural responses to acute stress and HPA axis activity. Life trauma may sensitize limbic-MTL regions and its related peripheral systems, which could compromise stress regulation and HPA axis function, and increase risk for negative stress-related health outcomes.